2017
DOI: 10.2147/jir.s142424
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of the ω3 polyunsaturated fatty acid derivatives resolvins E1 and D1 and protectin DX in models of inflammation and pain

Abstract: PurposeSpecialized pro-resolving lipid mediators (SPMs), also known as lipoxins, resolvins (Rvs), protectins and maresins, have been implicated in the resolution of the inflammatory process. However, a systematic comparison of their activity in the relief of inflammation and pain models is still lacking.Materials and methodsThe effects of Rvs E1 and D1 and protectin DX (PDX) were assessed in rat paws inflamed by the standard proinflammatory stimulus carrageenan or by histamine, 5-hydroxytryptamine, substance P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…RvE1 was also found to carry potent antinociceptive actions reducing inflammatory pain by regulating both central and peripheral responses with activities of 10 ng per mouse when administered intrathecally and 285–570 pmol when administered peripherally in vivo . These actions were also displayed in vitro at concentrations as low as 3 nM (Xu et al ., ; Jo et al ., ; Fonseca et al ., ). Of note, the antinociceptive properties of RvE1 are more potent than those exerted by the COX‐2 inhibitor NS398 and morphine (Xu et al ., ).…”
Section: The Identification and Structure Elucidation Of Novel Immunomentioning
confidence: 97%
“…RvE1 was also found to carry potent antinociceptive actions reducing inflammatory pain by regulating both central and peripheral responses with activities of 10 ng per mouse when administered intrathecally and 285–570 pmol when administered peripherally in vivo . These actions were also displayed in vitro at concentrations as low as 3 nM (Xu et al ., ; Jo et al ., ; Fonseca et al ., ). Of note, the antinociceptive properties of RvE1 are more potent than those exerted by the COX‐2 inhibitor NS398 and morphine (Xu et al ., ).…”
Section: The Identification and Structure Elucidation Of Novel Immunomentioning
confidence: 97%
“…The double lipoxygenase product 10,17-diHDHA denoted PDX is obtained via sequential steps of lipoxygenation to yield 10S,17S-diHDHA [33]. This PDX is an isomer of PD1 and has several actions on its own [60][61][62][63][64]. When PD1 is produced in neural systems, it is coined neuroprotectin D1 (NPD1), with protective actions demonstrated in retina, brain and pain [65][66][67].…”
Section: New Chemical Signals: Specialized Pro-resolving Mediator Supmentioning
confidence: 99%
“…Moreover, a recent study indicated that RvE1 influenced pain, a major symptom of RA, showing simultaneous anti-inflammatory and analgesic properties in experimental models closely related to translational sites in humans. 30 These studies have demonstrated the good therapeutic potential of RvE1 in many chronic inflammatory diseases. Indeed, RvE1 (Rx-10001) and its synthetic analog (Rx-10045) are currently under clinical trials for the relief of chronic dry eyes.…”
Section: Discussionmentioning
confidence: 98%